2021
DOI: 10.1177/03000605211004386
|View full text |Cite
|
Sign up to set email alerts
|

SELE gene as a characteristic prognostic biomarker of colorectal cancer

Abstract: Objective To investigate the expression and clinical value of the E-selectin gene ( SELE) in colorectal cancer (CRC). Methods Using gene expression profiles and clinicopathological data for patients with CRC from The Cancer Genome Atlas, and tumor and adjacent normal tissues from 31 patients with CRC from Xianyang Central Hospital, we studied the correlation between SELE gene expression and clinical parameters using Kaplan–Meier and Cox proportional hazards regression analyses. Results Higher expression of SEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Our results displayed that in general, CXCL1 in all samples was associated with a good prognosis of patients and this discrepancy seems to be due to not considering the high number of samples and classification of samples based on the stage in the relevant study [ 23 ]. In addition, studies have reported that high levels of SELE expression are associated with poor prognosis in patients with CRC [ 24 ]. These findings suggest that the expression of CXCL1 , SFTA2 , SELE , and SACS genes in CRC is highly heterogeneous and may be an important reason for the different prognoses of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results displayed that in general, CXCL1 in all samples was associated with a good prognosis of patients and this discrepancy seems to be due to not considering the high number of samples and classification of samples based on the stage in the relevant study [ 23 ]. In addition, studies have reported that high levels of SELE expression are associated with poor prognosis in patients with CRC [ 24 ]. These findings suggest that the expression of CXCL1 , SFTA2 , SELE , and SACS genes in CRC is highly heterogeneous and may be an important reason for the different prognoses of patients.…”
Section: Discussionmentioning
confidence: 99%
“…SELE , a member of selectin family, usually expressed on activated platelets and endothelial cells, exerts its effects in lymphocytes and monocyte recruitment, rolling, and diapedesis to the inflammatory areas 60 , 61 . Previous studies have demonstrated that SELE is associated with coronary artery disease 62 , coronary heart disease 63 , coal workers' pneumoconiosis 64 , hypertension 65 and colorectal cancer 66 . However, there was currently no research on SELE gene associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The SELE gene encodes E-selectin, which is found in cytokinestimulated endothelial cells and is thought to be responsible for the accumulation of leukocytes at sites of inflammation by mediating the adhesion of cells to the vascular wall (Li et al, 2021). Inflammatory factor interleukin-1 (IL-1), tumor necrosis factor-a (TNF-a), bacterial lipopolysaccharide (LPS) stimulated endothelial cells, the expression of E-selectin increased significantly, which can increase the permeability of blood vessel surface, promote the activation of inflammatory cells, and mediate the occurrence of inflammation (McEver, 2015).…”
Section: Analysis Of Target Functional Genes Related To Immune Responsementioning
confidence: 99%